Intestinal stem cells in the adult Drosophila midgut - Jiang, Huaqi; Edgar, Bruce (Experimental cell research, 2011)
Drosophila has long been an excellent model organism for studying stem cell biology. Notably, studies of Drosophila's germline stem cells have been instrumental in developing the stem cell niche concept. The recent discovery of somatic stem cells in adult Drosophila, particularly the intestinal stem cells (ISCs) of the midgut, has established Drosophila as an exciting model to study stem cell-mediated adult tissue homeostasis and regeneration. Here, we review the major signaling pathways that regulate the self-renewal, proliferation and differentiation of Drosophila ISCs, discussing how this regulation maintains midgut homeostasis and mediates regeneration of the intestinal epithelium after injury.